ANALISIS SWOT DALAM PENGELOLAAN TEMPAT WISATA DIKABUPATEN ROKAN HULU OLEH DINAS KEBUDAYAAN DAN PARIWISATA ROKAN HULU - Ainun Zaibah; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This research was conducted at the Department of Culture and Tourism Rokan Hulu. The purpose of this study was to analyze the SWOT in the management of the county rokan Places upstream by the department of Culture and Tourism Rokan Hulu. The usefulness of this study also as an input for the Department of Culture and Tourism Rokan Hulu and hoped this research can increase knowledge and and be a reference for further research with the same subject matter. In line with the purpose of this study, the population of this research is the Head of the numbered 1, Secretary totaled 1, Head of Tourism numbered 1, Section Head of Development numbered 1, section head of promotion numbered 1, section chief of facilities and infrastructure totaling 1 people, pariwista staff of 10 people and 50 visitor attractions. The Sampling Techniques for the head of the Department, Secretary, Head of Tourism, Head of Development Section, section head of promotion, sexy epala infrastructure, staff pariwista by way of the Census. As for visitor attractions by way of accidental sampling technique. Meanwhile, I use theory is a theory of Effendi (2014; 94) with the indicators of the Strengths, Weaknesses, Opportunities and Threats. After all analyzed by quantitative research SWOT analysis of the obtained results in the Management of Tourist Attractions in Rokan Hulu by the Department of Culture and Tourism Rokan Hulu is "Good Enough".